Order frequency as a variable to determine slow moving D items in ABC inventory categorization - Anthony Vaz; Anwar Tedjamulja; Akalpita Tendulkar; Premkumar Rajagopal (International Journal of Supply Chain Management, 2020)
â€” Many researchers have studied inventory models for deteriorating items that become waste or obsolete such as electronic components, food items and fashion goods [1], but a lot depends on how supply chain managers categorize finished goods and apply manufacturing strategies to overcome slow moving inventory. Process industries excluding pharmaceuticals, account for â‚¬2750 billion in revenues globally and inventories make up 56.7% of working capital for these industries [2]. According to Chase [3], Cisco had to write-off $1.2 billion worth of inventory due to holding too much of an item in finished goods. Tesco UK has admitted it had generated 30,000 tonnes of food waste in the first 6 months of 2013 [4]. The Food and Agriculture Organization of the United Nations (FAO) has indicated that about 32 percent of different types of food produced globally is lost or wasted. Supply Chain Managers need to look specifically at how inventory is categorized as order volume used in ABC inventory categorization can lead to items that are decreasing in popularity to be overly stocked. Many researchers have considered multiple variables in inventory categorization but this study aims to reiterate that the order frequency variable can be used to separate popular from non-popular finished goods inventory so that supply chain managers will be able to keep low inventory of such items and apply small batch and/or a fast response manufacturing strategy to reduce slow moving inventory within fast moving consumer goods (FMCG) businesses.